PENGARUH PENDIDIKAN AGAMA KRISTEN DISEKOLAH DALAM MEMBANGUN KARAKTER ANAK REMAJA - Ayuni Damai Daeli (Inculco Journal of Christian Education, 2022)
AbstractYear after year, there are many problems and incidents that befell every teenager, where juvenile crime cases are rampant; brawls between students, cases of bullying, rape as an illustration of the moral decline of teenagers in today's nation. This nation needs to provide the heart and space for the development of character education. The idea of character education brings fresh air to the world of education in Indonesia in overcoming the problem of adolescent moral decline. The planting of national character needs to be integrated in formal education, so that good values will be obtained in students from an early age.School as a place of education, where students are directed to efforts for someone to act or have insight into knowledge (normative). Learning is even more complex because it leads to the ultimate goal, namely that someone can behave or have a better personality (operational).Building a teenager's character means building a pattern of attitudes to be demonstrated in relation to one another. The attitude demonstrated is a characteristic of Christian morals.